Gender Specifics of Arab and Mongolian Students' Orderliness Manifestation - - Orsoo Tuya (Peoples' Friendship University of Russia (RUDN University), 2012)
The article highlights the results of a comparative study of the gender specifics of the manifestation of orderliness in Arab and Mongolian students.